Middle school superpowers : raising resilient tweens in turbulent times - Fagell, Phyllis L. (Hachette Go, 2023)
"Are you concerned that middle school will wreak havoc on your tween's well-being and sense of self? Wondering how you can ward off the decline in confidence research shows kids experience during these vulnerable years? Seeking strategies that will help your child emerge from middle school with even more resilience than when they started? From the author of Middle School Matters, which set up kids in grades 6 8 to thrive by developing social, emotional, and learning skills, Middle School Superpowers is all about resilience, which Phyllis Fagell, mental health therapist, certified school counselor and journalist, explains is often misunderstood. Fagell does not view it as a trait, like compassion or generosity. Instead, it involves its own set of skills to be better equipped to, as she says, "navigate future personal challenges and thrive in an increasingly turbulent world." With the new skills or "superpowers" detailed in Middle School Superpowers-including the power to "manage change and uncertainty"; "find your place and make strong connections"; "anticipate problems and make a plan"; "learn from missteps"; "recover from disappointment"; "know when and how to ask for help"; "set a reasonable pace and realistic goals"; and "identify the slivers of hope and humor"-Fagell helps parents raise confident, resilient kids by offering them practical, teachable, evidence-based ways they can support their child and foster their independence so they can leverage a range of typical middle school scenarios into the 12 skills they need to preserve their well-being and recover from any setback"--